A king helps out: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
This story depicts a compassionate king who chooses to serve his people rather than rule from a distance. By addressing their needs and showing kindness, he learns that true leadership comes from empathy and understanding, inspiring others to follow his example of generosity and humility.